1992
DOI: 10.1111/j.1600-0609.1992.tb01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelofibrosis in primary myelodysplasic syndromes

Abstract: In a retrospective study of 352 patients with primary myelodysplastic syndromes, 61 (17.3%) revealed myelofibrosis in bone marrow biopsies. The fibrosis was observed to occur mostly focally (41/61 cases), and collagen deposits were found very rarely (4/61). The histopathology of bone marrow biopsies revealed hyperplasia and disturbed differentiation in megakaryopoiesis; the frequency and grade of dysplasia in megakaryopoiesis increased with advancing myelofibrosis. Reticulin fibrosis occurred in all subtypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 27 publications
1
40
2
Order By: Relevance
“…We included only patients diagnosed with MDS, while those with primary myelofibrosis or overlap syndrome (MDS/MPS) were excluded from this analysis. The prognostic impact of bone marrow fibrosis in MDS patients has come into focus and several studies have confirmed a negative impact of fibrosis on survival [3][4][5][6][7] with some authors suggesting that MDS with fibrosis could be considered as a distinct entity. [9][10][11] Although bone marrow fibrosis is not included in the current prognostic risk scores such as the Allogeneic SCT for MDS with bone marrow fibrosis haematologica | 2011; 96 (2) 295 483 206 159 135 108 75 75 199 78 56 56 35 33 23 39 14 10 10 10 10 3 721 298 225 201 153 118 101 721 223 154 84 58 58 483 161 95 56 33 33 199 55 55 24 24 24 39 7 4 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included only patients diagnosed with MDS, while those with primary myelofibrosis or overlap syndrome (MDS/MPS) were excluded from this analysis. The prognostic impact of bone marrow fibrosis in MDS patients has come into focus and several studies have confirmed a negative impact of fibrosis on survival [3][4][5][6][7] with some authors suggesting that MDS with fibrosis could be considered as a distinct entity. [9][10][11] Although bone marrow fibrosis is not included in the current prognostic risk scores such as the Allogeneic SCT for MDS with bone marrow fibrosis haematologica | 2011; 96 (2) 295 483 206 159 135 108 75 75 199 78 56 56 35 33 23 39 14 10 10 10 10 3 721 298 225 201 153 118 101 721 223 154 84 58 58 483 161 95 56 33 33 199 55 55 24 24 24 39 7 4 4 …”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have shown that other factors, such as bone marrow fibrosis, provide additional information associated with poor outcome in MDS patients. [3][4][5][6][7] Allogeneic stem cell transplantation is now more frequently used as a curative treatment approach for MDS. The introduction of so-called dose-reduced conditioning regimens allows transplantation of patients up to the age of 70 years.…”
Section: Introductionmentioning
confidence: 99%
“…20 The results we present here confirm the prognostic importance of bone marrow fibrosis in patients with primary myelodysplastic syndromes. 1,[4][5][6][7] This adverse feature not only affected patients treated with non-transplant modalities but also patients who received hematopoietic stem cell transplant. The latter was in keeping with the study reported by Kroger et al 19 that severe bone marrow fibrosis was an independent risk affecting transplant outcome in patients with myelodysplastic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…3 In recent years, bone marrow fibrosis has been increasingly recognized as an adverse feature in patients with myelodysplastic syndromes, which correlates with increased risk of early bone marrow failure, transformation to acute myeloid leukemia, and an inferior patient outcome. [4][5][6][7][8] Some of these studies, however, preceded the European consensus criteria established for grading bone marrow fibrosis 9 and/or prior to the recent advent of therapeutic agents for myelodysplastic syndromes, such as lenolidomide and hypomethylating agents. In a study conducted by Della Porta et al, 5 patients with myelodysplastic syndromes who received hematopoietic stem cell transplantation or chemotherapy were censored at the time of therapeutic procedure.…”
mentioning
confidence: 99%
“…Although BM fibrosis can be seen in about 10-15% MDS patients and is a poor prognostic indicator, it is found more commonly in higher-risk cases and therefore only occasionally in RA [2][3][4][5][6][7]. Accordingly, recognizing that most cases of BM fibrosis occur in refractory anemia with excess (5-19%) blasts (RAEB) MDS, the current World Health Organization (WHO) Classification includes the provisional entry, RAEB with fibrosis (RAEB-F).…”
Section: Introductionmentioning
confidence: 99%